The Influence of Competence, Workload and Work Discipline on Civil Servant Performance - Andili, Alycia Hiko; Santoso, Soraya Nurfitrianni; Maryam, Siti (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study seeks to evaluate affects of competence, workload, and work discipline on performance of government employees within the agency. The research focused on a population of 150 permanent employees, from which a sample size of 110 was determined using Slovin formula with a 5% margin of error. Both interviews and questionnaires were used to obtain data. The study uses in addition to tests for validity, reliability, normality, multiple linear regression, coefficient of determination, t-tests, and f-tests to examine influence of each of the related independent variables on performance, both individually and jointly. The findings reveal that competence positively and significantly affects on employee performance, where as workload has a positive but statistically insignificant effect. Furthermore, a key and beneficial factor in increasing employee performance is work discipline. When analysed simultaneously, competence, workload and work discipline collectively demonstrate a substantial positive influence on employee performance, highlighting their importance in improving overall performance levels.